Analysis of The Effect of Audiolyfe Stimulation on Children's Appetite and Motor and Sensory Development - Fathiyah Ma'ani (Green Publisher Indonesia, 2024)
Stimulation in childhood plays an important role in supporting a child's physical, mental and social development. One type of stimulation that is gaining popularity is Audiolyfe, which is sound-based stimulation. However, this stimulation still needs to be tested to determine whether it can affect changes in children, such as appetite and motor and sensory development. This study aims to evaluate the effect of Audiolyfe stimulation on children's appetite and motor and sensory development. The research method used was quantitative with a quasi-experimental approach, where data were collected through observation and questionnaires. Data analysis was conducted using descriptive statistics. The results showed that Audiolyfe stimulation had a significant effect on children's appetite and motor and sensory development. Children who received this stimulation experienced improvements in appetite and motor and sensory skills. The findings indicate that sound-based stimulation such as Audiolyfe can be an effective method to support children's appetite and physical development.